Molecular differentiation in sympatry despite morphological stasis: deep‐sea Atlantoserolis Wägele, 1994 and Glabroserolis Menzies, 1962 from the south‐west Atlantic (Crustacea: Isopoda: Serolidae). (October 2014) - Brandt, Angelika; Brix, Saskia; Held, Christoph; Kihara, Terue Cristina
<x xml:space="preserve">Abstract</x> During DIVA‐3, the third expedition of the DIVA project (Latitudinal gradients of deep‐sea biodiversity in the Atlantic Ocean), 45 specimens of Serolidae were obtained from the Argentine Basin, at a depth of about 4600 m. These were a new species of Glabroserolis and Atlantoserolis vemae (Menzies, 1962). Besides the description of Glabroserolis occidentalis sp. nov., Glabroserolis specialis Menzies, 1962 is redescribed on the basis of the type material. Atlantoserolis vemae is redescribed using the type material, North Atlantic specimens, and the new South Atlantic material. Morphological differences between specimens of A. vemae from the North and South Atlantic could not be identified. The molecular data suggest that A. vemae from the Argentine Basin comprises two deeply divergent clades, which may represent reproductively isolated, sympatric species. © 2014 The Linnean Society of London